2013
DOI: 10.1016/j.autrev.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Complement associated pathogenic mechanisms in myasthenia gravis

Abstract: The complement system is profoundly involved in the pathogenesis of acetylcholine receptor (AChR) antibody (Ab) related myasthenia gravis (MG) and its animal model experimental autoimmune myasthenia gravis (EAMG). The most characteristic finding of muscle pathology in both MG and EAMG is the abundance of IgG and complement deposits at the nerve-muscle junction (NMJ), suggesting that AChR-Ab induces muscle weakness by complement pathway activation and consequent membrane attack complex (MAC) formation. This ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 152 publications
3
41
0
1
Order By: Relevance
“…A series of studies have suggested that accumulation of autoantibodies to AChR and subsequent activation of the complement cascade on postsynaptic membrane result in the assembly of membrane attack complex (MAC), thereby destroying AChRs and disrupting synaptic morphology (166, 171, 183) (Figure 5). It seems likely that complement-mediated destruction of the postsynaptic muscle membrane is more pathologically significant than antigenic modulation in MG pathogenesis (175, 184). These findings have promoted the development of novel therapies based on inhibition of complement pathways in MG treatment (185).…”
Section: Disruption Of Neural Transmission By Autoantibodiesmentioning
confidence: 99%
“…A series of studies have suggested that accumulation of autoantibodies to AChR and subsequent activation of the complement cascade on postsynaptic membrane result in the assembly of membrane attack complex (MAC), thereby destroying AChRs and disrupting synaptic morphology (166, 171, 183) (Figure 5). It seems likely that complement-mediated destruction of the postsynaptic muscle membrane is more pathologically significant than antigenic modulation in MG pathogenesis (175, 184). These findings have promoted the development of novel therapies based on inhibition of complement pathways in MG treatment (185).…”
Section: Disruption Of Neural Transmission By Autoantibodiesmentioning
confidence: 99%
“…Damage to the NMJ ion channels is autoantibody mediated where autoantibodies bind and result in the formation of the membrane attack complex consisting of C5b, C6, C7, C8, and C9 leading to muscular membrane damage and muscle weakness [2, 173]. The most common autoantibodies involved are anti-AChR antibodies presenting in 85% of patients, anti-muscle-specific kinase presenting in 5–8%, and anti-low density lipoprotein receptor-related protein in 2–46% of patients [69, 174, 175].…”
Section: Main Textmentioning
confidence: 99%
“…The major pathogenic mechanisms involve bivalent AChR autoantibodies cross‐linking adjacent AChR to cause accelerated AChR degradation (antigenic modulation) and complement‐mediated damage to the postsynaptic membrane (Baggi et al. ; Tüzün and Christadoss ; Ban and Phillips ). However, a proportion of MG patients instead express autoantibodies that target the extracellular domains of muscle‐specific (tyrosine) kinase (MuSK; Hoch et al.…”
Section: Introductionmentioning
confidence: 99%